2021
DOI: 10.1111/ppc.12761
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and positive determinants in nursing students after COVID‐19 alarm status: A descriptive cross‐sectional study

Abstract: Purpose To determine the relationship between posttraumatic growth (PTG), psychological flexibility, and psychological resilience of nursing students after the COVID‐19 alarm status. Design and Methods This descriptive cross‐sectional study was conducted with nursing students (N = 292) studying at a nursing school of a university. The data collection instruments included a form on descriptive variables, and the PTG, psychological flexibility, and psychological resilience scales. Descriptive statistics, indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
1
31
1
4
Order By: Relevance
“…Our study found that PTG levels of those stating that their family had good economic status were higher. There are similar results from other studies (Wang et al, 2014;Sörensen et al, 2019;Yıldız, 2021). Since students' good economic status has allowed them to easily cope with problems especially financial ones during the pandemic, this is believed to provide good support in the adaptation process to trauma.…”
Section: Discussionsupporting
confidence: 84%
“…Our study found that PTG levels of those stating that their family had good economic status were higher. There are similar results from other studies (Wang et al, 2014;Sörensen et al, 2019;Yıldız, 2021). Since students' good economic status has allowed them to easily cope with problems especially financial ones during the pandemic, this is believed to provide good support in the adaptation process to trauma.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research has shown evidence of posttraumatic growth in nurses who frequently cared for patients with COVID-19 ( Chen et al, 2021 ; Cui et al, 2021 ). Yildiz (2021) examined COVID-19 related posttraumatic growth in nursing students and found that nursing students exhibited higher posttraumatic growth scores than individuals exposed to earthquakes, diagnosed with breast cancer, or diagnosed with HIV. These findings indicate a coexistence between traumatic stress and posttraumatic growth in practicing nurses and in nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, a positive correlation between PTG and PR was assessed, this result is basically consistent with Hypothesis 1 and with previous research ( 19 ), in which a positive relationship between PTG and PR was found. A previous study examined the relationship between PTG and PR of nursing university students after the COVID-19 alarm status in Turkey and found a predictive effect of PR on PTG ( 66 ). However, the present result indicates that PTG is a significant predictor of PR, which potentially provides a novel perspective of the impact factor studies of PR.…”
Section: Discussionmentioning
confidence: 99%